8(x+2)+6=8x+7

Simple and best practice solution for 8(x+2)+6=8x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+2)+6=8x+7 equation:


Simplifying
8(x + 2) + 6 = 8x + 7

Reorder the terms:
8(2 + x) + 6 = 8x + 7
(2 * 8 + x * 8) + 6 = 8x + 7
(16 + 8x) + 6 = 8x + 7

Reorder the terms:
16 + 6 + 8x = 8x + 7

Combine like terms: 16 + 6 = 22
22 + 8x = 8x + 7

Reorder the terms:
22 + 8x = 7 + 8x

Add '-8x' to each side of the equation.
22 + 8x + -8x = 7 + 8x + -8x

Combine like terms: 8x + -8x = 0
22 + 0 = 7 + 8x + -8x
22 = 7 + 8x + -8x

Combine like terms: 8x + -8x = 0
22 = 7 + 0
22 = 7

Solving
22 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -1=x^2-12 | | 5(3c-3)=4c+5 | | 6(k-7)-2=5 | | 1+12x=21+x | | a^2=744-x^2+x^2 | | 8ax+bx=0 | | 8ax+bx+28a^2x^2+8abx^2=-36 | | -3(6y-10)-y=-4(y-3) | | 10x+2x=156 | | 3(x-12)=12x | | 3a^2x^2+8abx+4b^2=-36 | | 3x+46=-4x(x+6) | | 8(2x-5)=15 | | 37x+6=6(6x+8) | | 2x-6x+4=x-2+6 | | 0=x^3-12x+1 | | 0.07x=1790 | | 3x+46=4x(x+6) | | 300x=630 | | 0.02x=1710 | | 200x=540 | | 0.07x=1750 | | k-1.6=-0.4 | | 10*x^2-99*x+200=0 | | 3x+11=-31-3x | | 0.08x=1790 | | 0.05x=1720 | | =4.3*8.5 | | 0.03=1720 | | k+0.7=2.7 | | 3x=63x | | (-x+1)(x^4+6*x^2+9)=0 |

Equations solver categories